2002
DOI: 10.1128/iai.70.2.470-480.2002
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Dependent Differences in the Regulatory Roles of sarA and agr in Staphylococcus aureus

Abstract: The accessory gene regulator (agr) and the staphylococcal accessory regulator (sar) are central regulatory elements that control the production of Staphylococcus aureus virulence factors. To date, the functions of these loci have been defined almost exclusively using RN6390, which is representative of the laboratory strain 8325-4. However, RN6390 was recently shown to have a mutation in rsbU that results in a phenotype resembling that of a sigB mutant (I. Kullik et al., J. Bacteriol. 180:4814-4820, 1998). For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
176
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(199 citation statements)
references
References 52 publications
21
176
1
Order By: Relevance
“…We have previously demonstrated that RN6390 expresses RNAIII at elevated levels in comparison to UAMS-1 , and our microarray analysis confirmed that RN6390 expressed an increased level of the hld, agrA and agrB transcripts in the exponential growth phase in comparison to UAMS-1 (Table 3) (the agrC and agrD genes were not identified as upregulated in RN6390 versus UAMS-1 because the two strains possess different agr subtypes; Blevins et al, 2002). The hld transcript, which is included within the RNAIII effector molecule of the agr system (Janzon et al, 1989), was upregulated 9?4-fold within RN6390 relative to UAMS-1, in the exponential growth phase.…”
Section: Resultsmentioning
confidence: 49%
“…We have previously demonstrated that RN6390 expresses RNAIII at elevated levels in comparison to UAMS-1 , and our microarray analysis confirmed that RN6390 expressed an increased level of the hld, agrA and agrB transcripts in the exponential growth phase in comparison to UAMS-1 (Table 3) (the agrC and agrD genes were not identified as upregulated in RN6390 versus UAMS-1 because the two strains possess different agr subtypes; Blevins et al, 2002). The hld transcript, which is included within the RNAIII effector molecule of the agr system (Janzon et al, 1989), was upregulated 9?4-fold within RN6390 relative to UAMS-1, in the exponential growth phase.…”
Section: Resultsmentioning
confidence: 49%
“…In this study, we evaluated the regulation of the factor Bap by the global regulators agr and sarA. Examination of bap mRNA production by different strains at various growth phases showed that sarA was ences in the regulatory roles of sarA and agr in S. aureus (6). Another plausible explanation may be that spontaneous mutations in global regulator genes may occur in some isolates of S. aureus as has been found in S. epidermidis (42,43, and our unpublished results).…”
Section: Discussionmentioning
confidence: 96%
“…Similar to saeRS mutants (28), vfrB mutants show a marked reduction in Hla-dependent hemolytic activity when grown on rabbit blood agar, demonstrating decreased ability to produce Hla, and have enhanced production of V8 protease (26). Hla is under the control of multiple transcriptional and posttranscriptional factors (29)(30)(31)(32)(33)(34). Since Sae is known to be a major contributor to hla expression, we sought to determine whether changes in Hla activity in response to VfrB are in the same pathway as SaeRS or in independent pathways.…”
Section: Resultsmentioning
confidence: 99%
“…An additional explanation for this discrepancy in the necessity of VfrB for class I and class II promoters is that class I promoters have two SaeR-binding sites, whereas class II promoters have a single SaeR-binding site (14); therefore, higher levels of phosphorylated SaeR are required to activate class I promoters. Finally, in addition to the regulation of hla by SaeRS, several other master regulatory factors (e.g., Agr, RNAIII, Rot, SarA, and SarT) influence transcription of the hemolysin (29)(30)(31)(32)(33)(34), adding additional levels of regulation that affect expression. Thus, it is plausible that the complex regulatory mechanisms that control hla expression also contribute to VfrB having less effect on this class II gene than on coa.…”
Section: Discussionmentioning
confidence: 99%